Analisis Representasi Tekanan Sosial Peran Tokoh Mila dalam Film A Normal Woman - Kadek Ayu Purbaningrum; I Gusti Agung Alit Suryawati (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This study examines the representation of social pressure on women’s roles through a semiotic analysis of the character Mila in the film A Normal Woman (2025) by Lucky Kuswandi. Drawing on Stuart Hall’s Representation Theory and Lisa Tuttle’s Feminist Theory, this descriptive qualitative study with a critical paradigm uses primary data in the form of film dialogues and scenes, supported by relevant literature. The analysis, based on Roland Barthes’ model, reveals three layers of meaning—denotation, connotation, and myth—to examine visual and verbal signs that reproduce or critique patriarchal norms. The findings show that Mila is represented as experiencing layered social pressure due to her multiple roles as wife, mother, daughter, and daughter-in-law, which produce domestic and emotional burdens. The internalization of gender norms is reflected in the phenomenon of being a people pleaser, which is naturalized as “family harmony,” while bodily symbolism, such as nosebleeds and skin rashes, functions as a language of resistance against oppressive normality. The film simultaneously operates within reflective, constructionist, and intentional models of representation, while positioning women as a group disadvantaged by patriarchal structures, although it provides limited space for agency. The findings affirm the role of film as an arena for the reproduction and critique of social norms regarding gender, as well as its implications for interpersonal communication and the formation of contemporary women’s identities.